(3YbO GdJLGQI GdGdcJQhfjI (B/ s - (3aGOi eMeO YeGO GdOjf GHhGdSYhO Jhcds; (3SejMI GdbdjhHi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3NUU gPG GdHMK dJYQja GdJLGQI GdGdcJQhfjI hNUGFUgG hUhQgG heRGjGgG hGQcGf YbO GdJLGQI GdGdcJQhfjI ef MjK Jchjf GdJQGVi ef NdGd GdGjLGH hGdbHhd GdGdcJQhfi hef MjK UMI GdJQGVi MjK YjhH GdGOGQI GdGgdjI GddGRe ddJYGbO hGdeMd hGdSHH Ke JfGhd ReGf hecGf GHQGe gPG GdYbO ceG JfGhd JhKjb GdGOGQI ef NdGd OQGSI GdSLd GdGdcJQhfi hcPdc JfGhd GdHMK GdJMce haV efGRYGJ GdGKHGJ GdGdcJQhfis
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2008s
(3HHdjhLQGajG(B: (3UaMGJ (B261-272s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdJLGQI GdEdcJQhfjIs; (3YhGFb GdJLGQI GdEdcJQhfjI s; (3GdEjLGH GdEdcJQhfjs; (3GdbHhd aj YbO GdJLGQI GdEdcJQhfjIs; (3GdJhKjb hGdGKHGJ(B.s; (3GdSLd GdEdcJQhfjs; (3GdJhbjY GdEdcJQhfjs; (3GdGKHGJ GdEdcJQhfjs; (3GdJMcje GdEdcJQhfjs; (3MXQ GfcGQ GdYOGdIs; (3fXQjI GdecGf GdWdjbs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs